City Makers. Bologna and Emilia linear city. (Based on study projects at the Faculty of Architecture and Landscape, University Hannover in cooperation with the Department of Architecture, Alma Mater Studiorum, University of Bologna). - (:unkn) unknown (My University, 2019)
Die Arbeit erkundet die aktuellen Herausforderungen im urbanen Wandel der Stadt Bologna und ihren wachsenden Metropolenhorizont entlang der Via Emilia. Als Stadtforschungsprojekt wurde City Makers mit Studierenden der Universität Hannover in Zusammenarbeit mit der Universität Bologna entwickelt. Der Fokus auf Städtebau und Innovation hängt mit den tatsächlichen städtebaulichen und territorialen Planungsprozessen zusammen: dem Stadtinnovationsplan von Bologna und dem Aufbau von Neighborhood Labs sowie dem Strategieplan für die Metropole Bologna. Das Thema soziale Innovation wird zusammen gebracht mit bestehenden Initiativen und Projekten, wobei der Begriff des Maker Movements im Fokus steht.

City Makers explores current challenges in the urban transformation of the city Bologna and its expanding metropolitan horizon along Via Emilia. As urban research and design studio, City Makers has been developed with students of the University of Hannover, in cooperation with the University of Bologna. The focus on urban design and innovation is linked to actual urban planning and territorial planning processes: Bologna's Urban Innovation Plan and the setup of Neighbourhood Labs and the Strategic Plan for the Metropolitan City of Bologna. The topic of social innovation for increased citizens' participation and co-design - leading to new concepts and expertise in urban planning and design - in City Makers is set in dialogue with initiatives and concepts of making in the context of a highly productive and inclusive city and region, a strong university pole, and a rich industrial and artisan tradition.
Keywords: Universitätsstadt; Metropole; Stadtentwicklungsplanung; Stadtgestaltung; Stadterneuerung; Kreativwirtschaft; Stadtökonomie; Innovation; Partizipation; Kooperation; Reallabor; Entwurf; Forschungsprojekt; Sozialinnovation; Maker Movement